Intentional radiological exposure scenario evaluation by comparisons based on computer simulation - Carlos Eduardo S. Bonfim; Rodrigo D. Curzio; Gustavo G. Souza; Tercio Brum; José Carlos C. Amorim; Ubiratan C. Oliveira; Claudio Antônio Federico; Raquel Aparecida A. Costa e Oliveira; Jakler Nichele; Edson Andrade (Brazilian Journal of Radiation Sciences)
Nuclear or radiological mass incidents represent a threat that requires sophisticated coping strategies. This study aims to contribute by presenting a dual computational modeling methodology that juxtaposes numerical and analytical models to address a specific radioactive release scenario. This methodology seeks to extend beyond the theory underlying the modeling processes, favoring decision-making, especially in the early stages of such confrontation. This investigation applied a dual-model structure based on numerical methods and analytical techniques to simulate a radiological scenario promoted by activating a radiological dispersal device (RDD). It is important to emphasize that this methodology is not limited to RDD scenarios and is being proposed for application to any external release of radioactive materials. By evaluating and comparing the results of the simulations, particularly in areas close to the release point and in shorter time intervals, it is possible to verify the most appropriate model and identify scenarios in which the two models produce convergent results. The findings highlight the importance of estimating radiation doses, suggesting that such estimates can influence the understanding of radiological risks and their dependence on local atmospheric conditions. Careful interpretation and application of such results can mitigate epidemiological risks, enhance coordination capabilities, and stimulate the development of strategic responses.